Pakistan : Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver and Modification of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
This paper examines Pakistan's Fifth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver and Modification of Performance Criteria. Although most reforms were broadly on track, there were setbacks in energy sector reforms, and to a lesser extent in privatization. Progress was made in preparing the full Poverty Reduction Strategy Paper and monitoring intermediate social outcomes. All quantitative performance criteria for end-December 2002 were met. The budget for fiscal year 2003/04 will aim at a further reduction of the fiscal deficit while raising social and poverty-related expenditures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet